Systematically evaluate the effect of problem-based learning method in the teaching of epidemiology and health statistics in China - Yu, Xiangyuan; Linyuan Qin; Gongchen Huang; Xiao He (Journal of the Pakistan Medical Association, 2023)
Objective: To systematically evaluate the application of problem-based learning teaching in medical institutions. Methods: The systematic review was conducted in China following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and comprised search for relevant studies on July 31, 2020, of the China National Knowledge Infrastructure, Wanfang, China Biology Medicine disc, Web of Science, National Center for Biotechnology Information, Excerpta Medica Database and PubMed databases. Quality of the included studies was assessed as adequate, uncertain or inadequate based on the Cochrane Handbook for Systematic Reviews of Interventions. The teaching effects was evaluated using relative risk or standardised mean difference along with their corresponding 95% confidence intervals. Results: There were 3,447 students the 20 studies analysed; 1,681(48.8%) in problem-based learning group A and 1,766(51.2%) in lecture-based learning group B. Group A showed improved students’ test scores, learning interest, self-learning ability and collaboration skills (p<0.05). Conclusion: Problem-based learning teaching method showed advantages in terms of improvement in students’ professional knowledge and key learning skills. Key Words: Problem-based learning, Epidemiology, Statistics, Effect, Systematic evaluation.